Caries Risk Assessment: Cariogram-An Insight - Mohit Bansal; Ruhee Sangha; Simran; Navdeep Kaur Walia (International Healthcare Research Journal, 2019)
Dental caries is a public health problem. A new interactive graphical computorised system was introducted which is belived to record the caries risk assessment in less time depending of number of factors. This paper focus on the different sectors used in cariogram and its importance in reducing the caries risk.